Popular Culture / The Metropolitan Experience - Chambers Lain (Rouledge, 1986)
The writer shows how popular culture is continually being remade as each of us define our own urban space. Preface, Acknowledgements, Popular Culture and Popular Knowledge, The Obscured Metropolis, Urban Times, Urban Past Times, Inside the Present, The Sights, A World of Images, National Views, Other Visions and Screens and Pleasures, The Sounds, From Music Hall to Hitsville, Other Sounds and Other Worlds, Sounds of Youth, Conclusions, In These Times, Theoretical Exposures: Framing Culture, Further Materials, References, Index.